Efficacy and safety of antiangiogenic agents combined with HIFU in the treatment of advanced liver cancer - Wu, Rong; Shi, Qiuling; Liao, Dongbiao; Liao, Yao; Sun, Feng; He, Yu; Mao, Peiyang; Fan, Lingli; Bai, Yuxi; Feng, Gang (Frontiers in Oncology, 2025)
BackgroundAlthough antiangiogenic agents and HIFU (High-intensity focused ultrasound) are extensively used in the systematic treatment of advanced primary and secondary liver cancer, respectively, the efficacy and safety of their combination remain unclear. Thus, this study aimed to investigate the efficacy, safety, and synergistic effect of the combination of antiangiogenic drugs with HIFU in the treatment of advanced liver cancer.MethodsAdvanced liver cancer patients undergoing HIFU were included and matched 1:1 to two groups based on admission criteria: patients who received HIFU combined with antiangiogenic agents were assigned to the Combined HIFU group, whereas those who received HIFU but not antiangiogenic agents were assigned to the Only HIFU group. Then, therapeutic parameters, short-term efficacy, long-term survival, and safety of HIFU were analyzed and compared in this study.ResultsThere were 25 cases in both the Combined HIFU and Only HIFU groups. A significant difference was noted in the median ultrasound grayscale (hyperechoic region) occurrence time between the two groups (p=0.04). The coagulative necrosis rate, ORR, and DCR of liver lesions were numerically higher in the Combined HIFU group (60%, 64%, and 96%) than those in the Only HIFU group (44%, 36%, and 84%). Contrastingly, mOS did not differ significantly between the two groups. (HR,0.91; 95% CI, 0.45 to 1.82; p = 0.79). Finally, Acute adverse events (AEs) primarily included skin-burning pain, fever, and impaired liver function, and the incidence of infectious fever and impaired liver function was lower in the combined HIFU group.ConclusionAntiangiogenic agents combined with HIFU are effective and safe in the treatment of advanced primary and secondary liver cancer.